STUDY OF PHYSICAL CHEMICAL CHICKEN MEAT THAT IS SOLD IN SOME MARKET IN DENPASAR - I W. H., Astika; Miwada, I N. S.; Lindawati, S. A. (Jurnal Peternakan Tropika; Vol 5 No 2 (2017), 2017)
The purpose of this research is to analyze the quality of the chicken meats that are sold in some markets in Denpasar. The research was conducted over 3 months from September to November 2016. The research used Randomized block design (RBD) with 4 treatments and 4 times replications. The research used market as the treatment, Badung market is used as treatment B, Kreneng market as treatment K, Sanglah market as treatment S, Pemedilan market as treatment P. Chicken meats used in this research are the chests, which are collected from some traders in some markets in Denpasar city. Variable observed in this research include two aspects. Descriptive aspect is directly monitored in the process of physical pollution of chicken meat in the cutting process from beginning to end. Quantitative aspects include the value of pH , water holding capacity, cooking loss, and protein contents.The result showed that acidity/pH, water holding capacity, cooking loss and protein contents of meat were distributed at market samples (all treatments) were not significantly (P>0,05), normally and savety. Acidity/pH of meat at all treatments (S, K, B, dan P) had value 5.75, 6.02, 6.01, 6.03 respectively. Water holding capacity of meat were 15.81 % (S), 15.88 % (K), 13.46 % (B), 15.00 % (P). Cooking loss of meat on each treatments were 25.82 % (S), 25.50 % (K), 24.26 % (B), 25.46 % (P). The  protein contents of meat were 19.76 %, 20.15 %, 20.43 %, 19.99 % for treatments S, K, B, and P respectively. It was concluded that chicken meat were distribute on several market in Denpasar city had physical chemistry quality on broad of normally and savety for consumtion. Key words : chicken meat, physical chemistry quality , market